Penerapan Model Problem Based Learning (PBL) pada Materi Larutan Elektrolit dan Nonelektrolit untuk Meningkatkan Minat Belajar - Wiwin Rahmadhani; Suherman Suherman (Media Eksakta, 2022)
This study aims to increase student interest in learning in class X MIPA SMAN 1 Moutong through the application of the Problem Based Learning (PBL) learning model on electrolyte and nonelectrolyte solutions. The method in this study is a quantitative descriptive study. The subjects in this study were all students of class X MIPA 1 SMAN 1 Moutong totaling 36 people who were registered in the 2021/2022 academic year. The results showed that before carrying out learning using the Problem Based Learning model on electrolyte and nonelectrolyte solutions, the percentage of student interest in learning was 27.78% or included in the low category. The results of the teacher's observations obtained that the percentage of meeting 1 was 84.61% and the percentage of meeting 2 was 86.53%. The results of student observations obtained an average meeting 1 of 83.12% and an average of meeting 2 of 86.45%. Then after doing learning by applying the Problem Based Learning learning model on electrolyte and nonelectrolyte solution material, student interest in learning has increased, with the percentage of student interest in learning at 77.78% or in the high category. The conclusion of this study is that the application of the Problem Based Learning learning model on electrolyte and nonelectrolyte solutions can increase student interest in learning in class X MIPA SMAN 1 Moutong.